Meningkatkan Hasil Belajar Matematika Siswa Menggunakan Media Interaktif Powtoon Kelas V SDN 30 Ampenan - Nurmia, Lidia Zindarti; Andriayatno, Andriayatno; Fitriani, Fitriani; Munandar, Rizky (Lamda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Learning outcomes are a process in which individuals use cognitive, emotional, and psychomotor abilities to gather experiences over a relatively long period of time, gain knowledge, and then experience changes. This study aims to improve students' mathematics learning outcomes using interactive Powtoon media in grade V at SDN 30 Ampenan. This study uses a classroom action research (CAR) method with a population of 32 people conducted for 3 months, namely June to August. The results obtained showed an increase in learning outcomes of 81% using Powtoon media. Therefore, the use of interactive Powtoon media has a positive impact on improving elementary school students' mathematics learning outcomes. Powtoon media can be used by teachers as a way to provide broad understanding with the help of interactive videos.